A CONTRIBUTION OF FINANCIAL LITERACY ON FINANCIAL MANAGEMENT AMONG PERSONS WITH DISABILITY: FINANCIAL MANAGEMENT AMONG PERSONS WITH DISABILITY - Wolukawu, Ambrose (Student's Journal of Health Research Africa, 2025)
Persons with Disabilities (PwDs) face significant challenges in financial management, including low revenue generation, poor cost control techniques, and limited profitability and sustainability of their projects. These challenges are often linked to a lack of financial literacy, which hampers effective operational strategies. This study aimed to address the gap in empirical evidence by examining the contribution of financial literacy to the financial management of PwDs, focusing on VSLA group beneficiaries in Magale Sub-county, Namisindwa district. Specifically, it explored the impact of budgeting literacy, savings literacy, and debt management literacy on financial management. Using a Convergent Parallel design, the study combined quantitative and qualitative methods to collect data from 127 respondents, including VSLA beneficiaries, project management committees, and district officials. Stratified random sampling and purposive sampling techniques were employed. Data analysis involved descriptive statistics and Pearson Correlation coefficients. Findings revealed a strong positive relationship between financial literacy components—budgeting, saving, and debt management—and improved financial management among PwDs and their caretakers. The study concluded that enhancing these aspects significantly improves financial outcomes. It recommended strengthening financial literacy training and ensuring the sustainability of models like VSLA through increased funding and technical support. Further research was suggested to develop frameworks for model sustainability.